Effects of Brick and Aerated Concrete Infill Walls on Buildings - Bilir Ozhan, H.; Beklen, C.; Cagatay, I. H. (Engineering, Technology & Applied Science Research, 2019)
It has already been proved that infill walls have great impact on the behavior of the frame systems, especially under earthquake-like lateral loads. Infill walls are generally considered as partition members between spaces in concrete frame systems. They are generally included into calculations as dead loads exerted on beams, but they have various impacts on the behavior of frame-wall systems. Therefore, the well-known behavior of infill walls will have positive contributions. In the present study, a 10-story building was modeled with brick and aerated concrete infill walls. Window and door spaces were taken into consideration. Infill walls were modeled with the equivalent compression strut method. Changes in building rigidity, period, lateral displacement, base shear force and building behavior were investigated with relevant analyses.